(untitled) - Fay, James A. (New York, 2002)
This comprehensive text provides the scientific and technological background for understanding how ever-increasing use of energy threatens the natural environment at local, regional, and global scales and how this threat could be mitigated by more efficient use of conventional energy sources and their replacement by renewable energy sources. Designed for upper-level undergraduate and first-year graduate students, Energy and the Environment is essential reading for students and professionals in energy and environmental sciences and technology. Features BL Describes energy technologies and their effectiveness in transforming fossil, nuclear, and renewable energy into useful mechanical or electrical power BL Emphasizes the generation of electric power and the technological improvements that increase power generation efficiency and reduce air pollutant emissions from power plants BL Examines the use of energy in the transportation sector and how vehicle design and engine efficiency improvements could reduce fuel use and pollutant emissions BL Objectively surveys the field of renewable energy technologies and the prospects of increasing the share of renewable energy among all energy sources BL Analyzes the energy sources of toxic emissions to air, water, and land and their effects on environmental quality at local and regional scales BL Examines global climate change, energy consumption's contribution to it, and the salient technologies being developed to mitigate this effect BL Equips engineering majors, science majors, and professionals with the basic facts needed to develop solutions to these pressing environmental problems
Năng lượng và môi trường
Keywords: Power resources,Nguồn tài nguyên; Environmental aspects,Khía cạnh môi trường